(untitled) (Modern information system and technologies, 2018)
The article provides a detailed analysis of the existing distance learning system. Elementary elements of e-learning are considered, which represent a platform for monitoring and using resources in the learning process. A comparative analysis of the Learning Management System (LMS) and the LCMS Learning Content Management System (LCMS) has been carried out, and their disadvantages and advantages have been presented.